Federalismo, descentralização e democracia - Kerbauy, Maria Teresa Miceli [UNESP] (Universidade Estadual Paulista (Unesp), 2001)
Analisar a descentralização como transferência de poder decisório a municípios ou órgãos locais implica no entendimento dos municípios como entes federados, num país marcado pelas distorções federativas. Sistema representativo federal e participação popular local se intercruzam nesse processo, produzindo diferentes impactos na trajetória da descentralização no Brasil.

To analyse the decentralization as a decisive power transfer to the municipality or to the city counsil/local government implies the recognition of the municipalities as members of the federation, in a country where the idea of federation is almost distorted. In Brazil, representative system and popular participation cross each other, producing different turbulances in the way to decentralization.
Federalism, decentralization and democracy
Keywords: Decentralization; Federalism; Democracy; Local government; Descentralização; Federalismo; Democracia; Poder local